Optimalisasi Peran Mahasiswa KKN dalam Peningkatkan Sarana Olahraga dan Penguatan Silahturahmi Antar Desa - Abdul Basith Ridlo; Imelia Salsabila; M. Febian Syahputra; Rachma Dinda Kharisma; Maratus Syarifah; Rohmadi Rohmadi (CV. Doki Course and Training, 2025)
This community service activity aims to optimize the role of sports facilities as a medium for strengthening inter-village ties in the Ulak Banding area, South Indralaya District, Ogan Ilir Regency. The main problems faced by the community are the limited availability of adequate sports facilities and the lack of shared interaction spaces that can foster togetherness among villagers. The implementation method includes identifying community needs, repairing and procuring sports facilities, and implementing joint sports activities involving the village government and the local community. The results of the activity indicate that improving and utilizing sports facilities together can increase community participation in physical activity while strengthening social relations and a sense of togetherness between villages. This program also encourages the creation of a more harmonious social environment and contributes to improving the quality of life of the community. Thus, strengthening sports facilities can be an effective strategy in supporting community-based social development in rural areas.